River Areas Loss in Andalusia (1956-2007). A Scalar Approach. - González-Rojas, David (Revista de Estudios Andaluces, 2017)
Since the middle of the last century the river areas of Andalusia have undergone a process of degradation. This paper presents a historical and multiscale approach of the spatial distribution of river areas by using the land cover maps. At regional level, evidence of that Andalusia has lost a tenth of river areas over the last six decades. Secondly, analyzed of two local paradigmatic cases (Guadalmina river and Guadalquivir river) that can be extended to the rest of territory. The effort for the management of river areas has not been reflected in the results, being the interrelationships between water and land management (regional, sub regional and municipal) still an unresolved issue.